WETwin Factsheet 10. Case study: Ga-Mampa wetland, South Africa - (:unkn) unknown (My University, 2013)
This factsheet presents one of the case studies of the WETwin project : the Ga-Mampa wetland in South Africa. After a short description of the physical environment and main stakeholders, the factsheet gives the main results of the participatory multi-criteria analysis of the wetland management solutions, conducted with the stakeholders.
Keywords: African Research